2017
DOI: 10.1504/ijlic.2017.080640
|View full text |Cite
|
Sign up to set email alerts
|

Human capital development in socio-economic malaise: evidence from the UK

Abstract: Abstract:The purpose of this paper is to provide a novel insight into the role of knowledge-resources, particularly human capital, in times of socio-economic distress using a qualitative research approach. This is required because the social and economic environment has been transformed significantly in certain regions such as Europe since the global financial crisis humped in the fall of 2008. The study reveals how knowledge resources interact in building knowledge-eco society, how human intellectual capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Since IBs offer financial products and services that are compatible with Islamic doctrine, they need to invest equally in both firm-and industry-specific human capital, as it is desired for employees to excel in both economic and Shariah knowledge. This is supported by earlier research, which shows that investments in human capital affect a firm's ability to absorb new external knowledge, including that of alliance partners (e.g., Cohen and Kaimenakis, 2007;Nawaz, 2017d).…”
Section: Human Capital and Performancesupporting
confidence: 64%
“…Since IBs offer financial products and services that are compatible with Islamic doctrine, they need to invest equally in both firm-and industry-specific human capital, as it is desired for employees to excel in both economic and Shariah knowledge. This is supported by earlier research, which shows that investments in human capital affect a firm's ability to absorb new external knowledge, including that of alliance partners (e.g., Cohen and Kaimenakis, 2007;Nawaz, 2017d).…”
Section: Human Capital and Performancesupporting
confidence: 64%
“…Given the context of the present study, the human capital might be rare yet competent (Nawaz, 2017e;Nawaz, 2017f) given the significance of London as the financial hub for financial activities. Therefore, human capital efficiency is expected to have significant positive relationship with financial performance based on ROAA and ROAE.…”
Section: Human Capital Efficiencymentioning
confidence: 97%
“…The study showed that this is necessary because the social and economic environment has been transformed seriously in specific regions like Europe since the global financial crisis observed in the fall of 2008. The research reflected how knowledge resources interacted in building knowledgeeco society, how human intellectual capital comes to the scene under hard economic conditions, and how human capital can assist an economy to continue its fiscal position (Nawaz, 2017).…”
Section: Mehmet Lütfi Arslan Cevdet Kızılmentioning
confidence: 99%